PENETAPAN WAKAF (ITSBAT WAKAF) DI PENGADILAN AGAMA CILEGON (STUDI PERKARA NOMOR 281/PDT. P/2011/PA. CLG.) - Zainal Ridho (IAIN Batusangkar, 2017)
The purpose of this study was to analyze in depth and juridical consideration of the judge in the settlement process petition of Ithbat Waqf in Islamic court of Cilegon case number 281/Pdt.P/2011/Pa.Clg. Moreover, knowing the validity of nazhir and the position of heir of wakif in case petition of Ithbat Waqf that filed to Religion Court of Cilegon number 281/Pdt.P/2016/PA.Clg. This study was conducted in Islamic Court of Cilegon, using normative or doctrinal research method. Data were collected from the document and copy of the decree of Ithbat Waqf petition number 281/Pdt.P/2016/PA.Clg. and than re-check with interviewing judges who examine the cases and other participants that related with these case. The conclutions of this study, in general, the legal considerations of the judges are compliance with the provisions of applicable law example absolute authority, incidental power, Law of Waqf, writtten and witness evidence, changes allotment of waqf. But the considerations still incomplete because it doesn’t mention clearly the articles that used as the basis for deciding case of Ithbat Waqf, formal and material requirement of evidence, legal standing to litigate in case petition of Ithbat Waqf. Nazhir in this case has legal standing to litigate the petition Ithbat Waqf in Islamic court. And the involvement of the heirs in this case as a witness or as an anticipatory effort at a letter date if there is a dispute over land that has gained egal certainty from Islamic Court.